Information and Digital Development of Higher Education in the Conditions of Innovatyzation Economy of Ukraine - Нікіфоров, Петро Опанасович; Бабух, Ілона; Поченчук, Галина; Kateryna, Kraus; Kraus, Nataliia (My University, 2021)
The article deals with key measures of establishing information and digital development of the Institute of Education in the conditions of innovativeness of Ukrainian economy. The reason that motivated the study was a number of pressing issues, such as the formation of a highly qualified specialist with new quality of digital competencies and skills based on an effective innovation and entrepreneurship university and the establishment of a quality institute of digital education in European digital educational environment, which remain little studied and need knowledge. Among the goals pursued by authors is to identify the prerequisites for accelerating the automation and digitization of the economy at different levels of economic aggregation and in terms of economic sectors; to present author’s visualization of the potential innovative ecosystem of digital business center of the university in which applicants will be able to acquire digital practical skills. The purpose of the article is to investigate the peculiarities of modern problems of higher education in Ukraine, to consider objective conditions and current tendencies of development of information society. Methods: generalization – in studying the nature of digital education; structuring – in explaining the prerequisites for reforming digital principles. Results. The scientific publication reviews the features of modern problems of higher education in Ukraine, including: lagging of scientific developments from needs of the economy, fragmentation of the use of distance learning technologies in economic specialties, inconsistency of the laboratory base of universities with a technical profile of the level of modern technologies. Scientific analysis of paradigm change in education of Ukraine is conducted. Authors’ opinion is: changes are caused by integration processes in higher education system, democratization of the process of obtaining education, introduction of tools of freedom of choice of resources, technologies. The originality of publication is that authors argue that a transformational change at the Institute of Education is a change from a passive system where learning is an audition, to an active learning system where students learn subjects/disciplines by sharing knowledge about these subjects. Value of the article is that authors outlined main areas of use of digital information technology in higher education, namely: development of educational websites and promising tools, teaching methods and technologies with a focus on development, promotion of personalized education. Conclusions. The article is devoted to the consideration of objective conditions and current tendencies of development of information society, which determine the course of automation and digitization of the provision of educational services in the conditions of innovativeness of Ukrainian economy.
Keywords: information and digital development; higher education; informatization of the economy; informatization of education